Activation of NF-kB-Mediated TNF-Induced Antimicrobial Immunity Is Required for the Efficient Brucella abortus Clearance in RAW 264.7 Cells - Huynh T. Hop; Alisha W. B. Reyes; Tran X. N. Huy; Lauren T. Arayan; WonGi Min; Hu J. Lee; Man H. Rhee; Hong H. Chang; Suk Kim; Suk Kim (Frontiers in Cellular and Infection Microbiology, 2017)
In this study, we explore the regulatory roles of pro-inflammatory cytokine tumor necrosis factor alpha (TNF) in the innate immunity of macrophages against B. abortus infection. We show that infection of macrophage with B. abortus induces marked expression and secretion of TNF which subsequently binds to TNF receptor 1 (TNFR-1) and activates a downstream signaling cascade of the innate immunity. Blocking of TNF signaling resulted in a notable increase of B. abortus survival which was associated with an increase of anti-inflammatory cytokine interleukin 10 (IL-10), a beneficial effector of Brucella survival, as well as remarkable decrease of reactive oxygen species (ROS) and nitric oxide (NO), antibrucella molecules. However, surprisingly, the interference of TNF did not show any influence on phagolysosome and cell death events. Furthermore, the transcriptional factor NF-kB was found to be a main mediator of TNF signaling when blocking of NF-kB pathway drastically suppressed the TNF-induced brucellacidal effect. Taken together, these findings clearly indicate that the immune cascade activated by TNF/TNFR-1 is required for the sufficient resistance to B. abortus survival in macrophages.